Testing elite XC skiers with use of wearable sensor technology - Losnegard, T. (Post Olympic Winter Games 2018, Vuokatti, 28.-29.6.2018, 2018)
Using wearablesensor technologyin elite XC skiers - with focuson GPS systems • Valid GPS-systems for XC skiing? • Examplesf rom studies • "Influence of pole lengths on performance tested on snow" • "Exercise intensity in distance XC skiing race" • Comments/ questions